Ketertarikan Muda Mudi pada Media Sosial Instagram: Studi Kasus Barombong Kecamatan Tamalate Kota Makassar - Mrs. Nurlela; Mr. Asmunandar (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2022)
This study aims to determine the interest of young people in social media Instagram, the implications and values ​​for society. This study uses qualitative research methods with observation techniques, in-depth interviews, and in-depth analysis to obtain the desired data. Interviews were conducted with several informants who have different backgrounds and are active in using Instagram social media and have been using Instagram for more than 5 years. The results of this study indicate that: (1) young people's interest in social media Instagram is different and has its own characteristics. (2) Instagram users can have a positive or negative impact depending on the user and how to use it. One way to make Instagram use positive is to limit Instagram usage and to prevent users from wasting their productive time, users can take advantage of the "set daily time limit" feature in Instagram settings. (3) The implications of good use of Instagram social media can develop personal motivation and interest, get the latest information, a place to hone skills, and seek new knowledge that is relevant to the interests of the accounts that are followed. However, Instagram can turn negative if used inappropriately. The use of Instagram can make users go crazy, so they waste a lot of productive time, and many posts have the potential to cause hoaxes or other negative things, so we need to be vigilant and careful about these things.